2020
DOI: 10.3390/ijerph17113765
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Capacity-Building Efforts to Address Environmental Justice Concerns

Abstract: Environmental justice (EJ) efforts aimed at capacity building are essential to addressing environmental health disparities; however, limited attention has been given to describing these efforts. This study reports findings from a scoping review of community–academic partnerships and community-led efforts to address environmental inequities related to air, water, and land pollution in the United States. Literature published in peer-reviewed journals from January 1986 through March 2018 were included, and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Research methods for the systematic search and scoping review are described in Williamson et al [61]. In brief, 58 peer-reviewed studies published from January 1986 to March 2018 are used in the review and detail community-academic partnerships and community-engaged efforts employed to address environmental inequities related to air, land, and water pollution in the United States (see Appendix A Figure A1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research methods for the systematic search and scoping review are described in Williamson et al [61]. In brief, 58 peer-reviewed studies published from January 1986 to March 2018 are used in the review and detail community-academic partnerships and community-engaged efforts employed to address environmental inequities related to air, land, and water pollution in the United States (see Appendix A Figure A1).…”
Section: Methodsmentioning
confidence: 99%
“…A standardized form was used to extract relevant data that identified the policy, system, or environmental (PSE) change target [62,63]; capacity-building and community change strategies; and levels of community engagement. Additional abstraction measures (further detailed in Williamson et al, 2020) include author discipline, research design, study setting, and population demographics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By leveraging the skills and knowledge of both community members and researchers, CBPR improves the applicability and use of research findings. In public health, the approach is utilised as a means to improve community health and well-being (Israel et al, 1998) and it is often used as a strategy for building community capacity to address environmental health concerns (Williamson et al, 2020). In line with CBPR principles, the research topic for this study was identified by community members and data collection was carried out by both academic researchers and community organisation staff.…”
Section: Methodsmentioning
confidence: 99%